2008
DOI: 10.1093/jn/138.2.272
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Cholesterol from Eggs Increases Plasma HDL Cholesterol in Overweight Men Consuming a Carbohydrate-Restricted Diet ,2

Abstract: Carbohydrate-restricted diets (CRD) significantly decrease body weight and independently improve plasma triglycerides (TG) and HDL cholesterol (HDL-C). Increasing intake of dietary cholesterol from eggs in the context of a low-fat diet maintains the LDL cholesterol (LDL-C)/HDL-C for both hyper- and hypo-responders to dietary cholesterol. In this study, 28 overweight/obese male subjects (BMI = 25-37 kg/m2) aged 40-70 y were recruited to evaluate the contribution of dietary cholesterol from eggs in a CRD. Subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
122
1
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(152 citation statements)
references
References 36 publications
15
122
1
7
Order By: Relevance
“…As for the location, Italy [16][17][18] contributed with three studies; the United States [19][20][21][22][23] 16,25,28 , and two with partially blind intervention 17,20 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the location, Italy [16][17][18] contributed with three studies; the United States [19][20][21][22][23] 16,25,28 , and two with partially blind intervention 17,20 .…”
Section: Resultsmentioning
confidence: 99%
“…As to the population, four trials studied outpatients from only one hospital 18,22 ; two were multicentric 24,29 ; two studied population representative of communities 16,30 ; three studied patients picked up by newspaper advertisements 19,2526 ; one studied university employees 20 ; and three did not inform the population studied 21,23,27 . The prevalence of MS was the main outcome in six studies 16,[24][25][26]29,30 and secondary when the prevalence of MS components [18][19][20][21][22]27,28 , weight reduction 23 and behavior of inflammatory markers and endothelial function 17 function were the primary outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Feskens and Kromhout (27) studied 394 non-diabetic men (aged 50-70 years) in the Zutphen Study and found that saturated fat and dietary cholesterol intakes may affect glucose tolerance detrimentally. However, in their investigation of twenty-eight overweight or obese male patients (aged 40-70 years) on a carbohydrate-restricted diet, Mutungi et al (28) found that use of 3 eggs/d had no effects on fasting glucose compared with no egg consumption. On the other hand, Pearce et al (29) studied sixty-five participants with type 2 diabetes or impaired glucose tolerance and investigated the effect of a hypoenergetic high-protein/high-cholesterol diet v. a diet with a similar amount of animal protein (high-protein/ low-cholesterol) on plasma lipids, glycaemic control and cardiovascular risk markers.…”
Section: Discussionmentioning
confidence: 99%
“…Others have indicated that egg intake increases both HDL-C and LDL-C and hence, does not affect the L/H cholesterol ratio (12,13). With a weight loss intervention, consuming 3 eggs per day resulted in no increases in LDL-C while a significant increase in HDL-C was observed in overweight men (14). Blesso et al reported that whole egg consumption improved lipoprotein profiles and insulin sensitivity to a greater extent than yolk-free egg substitute in individuals with metabolic syndrome (15).…”
Section: Discussionmentioning
confidence: 99%